2014
DOI: 10.1007/s11910-014-0479-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Olfactory Challenge Tests in Incipient Dementia and Clinical Trial Design

Abstract: The brain changes associated with Alzheimer's disease (AD) develop slowly over many years before the onset of dementia. Biomarkers for AD that allow its detection during this clinically silent phase will be hugely important when disease-modifying treatments that halt or slow its progression become available. Early detection, leading to early treatment, may in some cases avert dementia. Biomarkers aid our understanding of the presymptomatic stages of the disease and enable the identification of individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Evidence suggests that one of the earliest events in the AD-related degenerative process is involvement of the olfactory bulb and tract. 24 Olfactory bulb concentrations of tau, b-amyloid, and a-synuclein have been shown to significantly increase with the Braak stages, 3 and the degree of tau, b-amyloid, and a-synuclein pathology in the olfactory bulb has been shown to reflect the degree of respective pathologies in other brain regions, 25 suggesting a potential role for olfactory testing as a severity and progression marker in AD. 4 Deficits in OI precede impairment on olfactory threshold detection tasks 26 and remain after cognitive measures and odor detection deficits are controlled for, 5 suggesting a pathophysiologic process that originates near the central olfactory structures in the medial temporal lobe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that one of the earliest events in the AD-related degenerative process is involvement of the olfactory bulb and tract. 24 Olfactory bulb concentrations of tau, b-amyloid, and a-synuclein have been shown to significantly increase with the Braak stages, 3 and the degree of tau, b-amyloid, and a-synuclein pathology in the olfactory bulb has been shown to reflect the degree of respective pathologies in other brain regions, 25 suggesting a potential role for olfactory testing as a severity and progression marker in AD. 4 Deficits in OI precede impairment on olfactory threshold detection tasks 26 and remain after cognitive measures and odor detection deficits are controlled for, 5 suggesting a pathophysiologic process that originates near the central olfactory structures in the medial temporal lobe.…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory testing may be a simple, inexpensive, and highly sensitive method of identifying older adults at risk for developing dementia, particularly when combined with other early markers. [1][2][3] While it is well established that olfactory deficits are present in symptomatic Alzheimer disease (AD), 4 recent studies have demonstrated that deficits in olfactory functioning occur very early in the disease process, often preceding the onset of other clinical symptoms. 5 In addition, several studies have reported that olfactory deficits in cognitively normal older adults are associated with increased risk for cognitive decline and dementia.…”
mentioning
confidence: 99%
“…6,7 Further potential mechanisms for this improvement of appetite in patients with AD might be both the inflammatory effects of ChEI in cholinergic pathways, and their ability to improve smell and taste perception by increasing the acetylcholine concentration in olfactory mucosa and taste buds, respectively. 24,25 In addition to rivastigmine's inhibition of ChE, it might further contribute to improved swallowing by inhibiting BuChE. 9 All of these potential mechanisms serve as targets for illumination by future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been reported that AChEIs might improve nutritional aspects through anti-inflammatory effects over cholinergic pathways and their improving sensation of smell and taste 5 51. Moreover, improvement in swallowing function due to increased acetylcholine concentration by AChEIs may have an additional role in improving nutritional aspects 52…”
Section: Discussionmentioning
confidence: 99%
“…One is the occurrence of repeated actions and behavioural disorders due to episodic memory and impairment in attention resulting in increased energy loss in patients with dementia 3. Another potential explanation is alteration of the sensation of smell and taste in addition to impaired swallowing function due to cholinergic deficits 4 5. Cognitive deterioration affects daily functional status and instrumental activities which result in disability, dependence and decreased oral intake 6.…”
Section: Introductionmentioning
confidence: 99%